ANALISIS TINGKAT PENGANGGURAN TERBUKA DI PROVINSI JAWA BARAT TAHUN 2014-2024 - Sinta Meilinda; Putri Cahyani; Sri Ningsih (Jurnal Riset Multidisiplin Edukasi, 2026)
Unemployment remains a major issue in economic development in many countries, including Indonesia. One important indicator used to describe labor market conditions and the economy's ability to absorb the labor force is the Open Unemployment Rate (OUR). This study aims to analyze the development of the Open Unemployment Rate (OUR) in West Java Province during the period of 2014-2024 and to examine West Java Province's position compared to the national labor market. This study employed a quantitative descriptive method using secondary data obtained from the Badan Pusat Statistik (BPS). The analysis shows that the Open Unemployment Rate (OUR) in West Java Province fluctuated during the study period. In 2020, a significant increase occurred due to the impact of the COVID-19 pandemic, with the Open Unemployment Rate (OUR) reaching 10,46%. This condition indicates that labor market dynamics are influenced by several factors, such as economic growth, the size of the labor force, employment opportunities, and the availability of jobs. Therefore, the analysis of the Open Unemployment Rate (OUR) is crucial as a basis for formulating effective and targeted employment policies to reduce unemployment and increase employment opportunities.